2022
DOI: 10.1038/s41598-022-11868-4
|View full text |Cite
|
Sign up to set email alerts
|

The bromodomain inhibitor JQ1 up-regulates the long non-coding RNA MALAT1 in cultured human hepatic carcinoma cells

Abstract: The epigenetic reader, bromodomain-containing 4 (BRD4), is overexpressed in hepatocellular carcinoma (HCC), and BRD4 inhibition is considered as a new therapeutic approach. The BRD inhibitor JQ1 is known to inhibit the enrichment of BRD4 at enhancer sites. Gene network analyses have implicated long non-coding RNAs (lncRNAs) in the effects of JQ1, but the precise molecular events remain unexplored. Here, we report that in HepG2 cells, JQ1 significantly reduced various proliferation-related lncRNAs, but up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Our differential expression analysis of genes had identified 193 differentially expressed lncRNAs, of which 162 genes were identified as SE-lncRNAs and 15 SE-lncRNAs were differentially expressed. In line with our finding, a plethora of evidence supports that JQ1 can alter the expression profile of lncRNAs in cancer cells and exert a critical role in the proliferation inhibition of cancers ( Baek et al, 2022 ; Choi et al, 2022 ; Liu et al, 2021 ). The general consensus is that lncRNAs exert physiological regulatory effects by regulating mRNAs.…”
Section: Discussionsupporting
confidence: 91%
“…Our differential expression analysis of genes had identified 193 differentially expressed lncRNAs, of which 162 genes were identified as SE-lncRNAs and 15 SE-lncRNAs were differentially expressed. In line with our finding, a plethora of evidence supports that JQ1 can alter the expression profile of lncRNAs in cancer cells and exert a critical role in the proliferation inhibition of cancers ( Baek et al, 2022 ; Choi et al, 2022 ; Liu et al, 2021 ). The general consensus is that lncRNAs exert physiological regulatory effects by regulating mRNAs.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies demonstrated that JQ1, a small molecule, can specifically dislodge BRD4 from enhancers, thereby dissolving mediator and RNAPII clusters ( 50 , 51 ). Treatment with JQ1 can cause reconfiguration of chromatin structure in selected gene loci ( 52 ). We observed a significantly diminished ligation efficiency in the same region following JQ1 treatment, indicating that the interaction observed between the transcription start site region of AKR1C1 and the distal G4 is P–E interaction.…”
Section: Resultsmentioning
confidence: 99%
“…For this study, we used the RNA-seq data of our previous paper (GSE155408). To identify DElncRNAs, a comprehensive reference list of known lncRNAs was included in the processing of the RNA-seq data [ 10 , 35 , 36 ]. Briefly, FASTQ data were quality controlled and trimmed with Trimmomatic (version 0.36) [ 37 ].…”
Section: Methodsmentioning
confidence: 99%